Optimization of relational capital and the strength of SMEs network collaboration to improve its performance: Evidence from Indonesia - Murry Harmawan Saputra; Luki Adiati Pratomo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study aims to develop a conceptual model framework that elucidates strategies for enhancing the performance of SMEs using a network theory approach. The novelty lies in developing a conceptual model that proposes the strength of SMEs network collaboration as an intervening variable, addressing the gap in the literature regarding the impact of relational capital on its performance. The study involves 238 SMEs in six regencies in Central Java and the Special Region of Yogyakarta, Indonesia. The majority of the proposed hypotheses are supported, indicating that relational capital, quality of value co-creation, voluntary knowledge sharing, and the strength of network collaboration significantly improve SMEs performance. The results validate the logical connection between the variables and clarify the reference theories. Additionally, the conceptual model is suitable for capturing business phenomena in the field, making it a valuable reference for SME development in Indonesia and other emerging market countries.